1987
DOI: 10.1095/biolreprod36.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Follicle-Stimulating Hormone-Induced Ovulation by Indomethacin in the Perfused Rat Ovary1

Abstract: In isolated, perfused ovaries of rats treated with pregnant mare's serum gonadotropin (PMSG), purified preparations of ovine follicle-stimulating hormone (FSH) (oFSH-211B) and rat FSH (rFSH-I-6), 100 ng/ml, were found to induce ovulations (4.8 +/- 0.9, n = 4, and 6.4 +/- 2.0, n = 5, ovulations per ovary, respectively). Indomethacin (5 micrograms/ml) added to the perfusate inhibited this ovulatory effect and exogenous prostaglandin F2 alpha (PGF2 alpha) (1 microgram/ml), or prostaglandin E2 (PGE2) (0.5 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The cyclooxygenase (COX)-2 enzyme, which catalyzes the rate-limiting step in intrafollicular prostanoid synthesis, is induced within the granulosal layer of rat (Sirois et al 1992), equine (Sirois & Dore 1997) and bovine preovulatory follicles (Sirois 1994, Tsai et al 1996 in response to the LH surge. Indomethacin (INDO), an inhibitor of the COX pathway, is a potent inhibitor of ovulation in numerous species (Tsafriri et al 1972, Murdoch et al 1986, Sogn et al 1987, including cattle (De Silva & Reeves 1985). Mice with a targeted mutation in the COX-2 gene are infertile (Dinchuk et al 1995) and anovulatory (Davis et al 1999), potentially due to a proteoglycan synthesisrelated alteration in cumulus expansion and impaired follicle rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclooxygenase (COX)-2 enzyme, which catalyzes the rate-limiting step in intrafollicular prostanoid synthesis, is induced within the granulosal layer of rat (Sirois et al 1992), equine (Sirois & Dore 1997) and bovine preovulatory follicles (Sirois 1994, Tsai et al 1996 in response to the LH surge. Indomethacin (INDO), an inhibitor of the COX pathway, is a potent inhibitor of ovulation in numerous species (Tsafriri et al 1972, Murdoch et al 1986, Sogn et al 1987, including cattle (De Silva & Reeves 1985). Mice with a targeted mutation in the COX-2 gene are infertile (Dinchuk et al 1995) and anovulatory (Davis et al 1999), potentially due to a proteoglycan synthesisrelated alteration in cumulus expansion and impaired follicle rupture.…”
Section: Introductionmentioning
confidence: 99%
“…In the first approach, classical non-steroidal anti-inflammatory drugs (NSAIDs), inhibiting both COX-1 and COX-2 activity, as well as the more recently developed selective COX-2 inhibitors, have been repeatedly reported to inhibit ovulation in all mammalian species investigated so far (reviewed by Brännströ m & Janson 1991, Tsafriri et al 1993, Espey & Lipner 1994. Furthermore, exogenous prostaglandin supplementation restored ovulation in NSAID-treated animals, at least under some experimental conditions (Holmes et al 1983, Sogn et al 1987, Gaytán et al 2002a). More recently, genetic studies in mice (Lim et al 1997, Matsumoto et al 2000 have confirmed the obligatory role of COX-2/ prostaglandins in ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the presence of functional FP receptors has never been reported for follicular granulosa cells of any mammalian species. Disruption of the PGE2 receptor EP2 reduces the efficiency of ovulation in mice (Hizaki et al 1999), and previous studies support a role for PGE2 to regulate periovulatory events in mammals (Sogn et al 1987, Peters et al 2004, including primates (Duffy & Stouffer 2002). It remains possible that either or both PGE2 and PGF2a may be able to initiate ovulatory events in the follicles of primates and domestic animals.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of PGF2a to PG-synthesis inhibitor-treated animals can restore ovulation in rodents, domestic animals, and primates (Wallach et al 1975, Murdoch et al 1986, Sogn et al 1987, Janson et al 1988. However, disruption of FP receptor expression did not prevent ovulation in mice (Sugimoto et al 1997), arguing against receptormediated action of PGF2a to initiate ovulatory events in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation